Tributaç\~ao indireta: Alíquotas efetivas e incidência sobre as famílias - Fernando Gaiger Silveira; Theo Ribas Palomo; Felipe Moraes Cornelio; Marcelo Resende Tonon (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The text presents estimate of the tax incidence, especially the indirect one, on the income of families according to data from the last Consumer Expenditure Survey (POF) of 2017-2018. For this purpose, the values of the taxes on income and equity calculated in the survey are used, as well as expenditure on consumer goods and services, to which effective indirect tax rates are applied. The tax rates are estimated based on a developed methodology that considers the taxes on inputs and capital goods present in the final demand products, based on the Input-Output Tables. A translator is also developed between the table products and the countless goods and services whose consumption is determined in the POF. The results show that the regressive effect of indirect taxes predominates in the redistributive effect of the tax system as a whole, that is, it surpasses the small redistributive effect of direct taxation. The aim is also to identify the most burdened expenditure items and the effects of the design of indirect taxes, which include exemptions and lower incidences, on the regressive nature of indirect taxes. At the end of the paper, it is argued that the path to greater equity is to expand direct and its progressivity, keeping in mind that indirect taxes are a key part of social protection in a country that has been showing a positive redistributive performance.
10419/284879
Keywords: D31; D63; H22; H23; 330; Indirect taxation; income distribution; tax incidence